Aspectos da ecologia comportamental de Dinoponera quadriceps (Hymenoptera, Formicidae, Ponerinae) - Andrade, Andreza Cristina da Silva (2010)
The genus Dinoponera has its distribution in South America. The genus has only six species and characterized by the secondary loss of the queen. In this group, there is no caste division and the reproduction is performed by a mated worker (gamergate). The objectives of this study were to investigate the division of worker, focusing the ontogeny of the behaviors and their relationship with the social structure of this species. The colonies were collected and maintained in artificial nests in the Laboratório de Entomologia da Universidade Federal de Sergipe. We made a behavioral catalogue with 2688 behavioral acts. The period of observation of colonies and the variation of colonies were not enough to support age poliethism. The cluster analysis showed that there was little fidelity of formed groups. The results suggest that there is a higher number of generalists, i.e. workers that performed all tasks rather.